Islamic rules and guidelines for using digital technology to support sustainable development goals - Mohamad Shauki, Aziyah; Busari, Saheed Abdullahi; Ibrahim Mohamed, Hossam El Din; Ali Mukred, Muaadh Mustafa (USIM Press, 2025)
This study illustrates the Islamic rules and guidelines that govern the use of digital tools to support sustainable development goals (SDGs) during this rapid advancement of digital technologies. As the world realizes that digital tools have crucial benefits to their users, no one can deny their benefits, like software and online resources that help people do many tasks easily. These tools help people to be more productive and effective, work together, and communicate better from anywhere and everywhere. However, these beneficial tools can also have bad consequences if they are misused. The paper explores the five categories of Islamic legal rulings that can apply to individual uses of digital tools: obligation (Wajib), recommendation (Mandub), permissibility (Mubah), disapproval (Makruh), and prohibition (Haram). It argues that the use of modern technology does not conflict with Islamic law but rather can be considered a means to achieve the objectives of Islamic jurisprudence. Furthermore, the paper suggests eleven guidelines for using digital technology, starting from "good intention" (al-niyyah al-salihah) as a crucial guideline for Muslims in interacting with digital tools. By aligning the use of technology with the intention of achieving legitimate benefits for oneself and society, without causing harm or committing forbidden acts, Muslims can transform their interaction with digital tools into acts of worship that bring them closer to Allah. The study concludes with a discussion on how the principled use of digital technology, grounded in Islamic ethical frameworks, can contribute to the realization of some of the Sustainable Development Goals (SDGs). This holistic approach positions the Muslim community as a key partner in the global quest for a more just, equitable, and environmentally sustainable future.